Two cases of interparietal inguinal hernias undergoing laparoscopic treatment: a case series. Issue 2 (14th February 2023) - Ozawa, Hiroki; Hara, Asuka; Hayashi, Keita; Kaneko, Yasushi; Kikuchi, Hiroto; Fujisaki, Hiroto; Hirata, Akira; Hongo, Kumiko; Takano, Kiminori; Suga, Atsushi; Yo, Kikuo; Yoneyama, Kimiyasu; et al.
Abstract: Interparietal inguinal hernia, an exceedingly rare type of inguinal hernia in which the hernia sac anatomically lies between the tissue layers of the abdominal wall, is difficult to diagnose from physical findings. Given the few reports on interparietal inguinal hernias, this condition has remained fairly unrecognized. Herein, we report the successful imaging and laparoscopic diagnoses as well as repair of an interparietal inguinal hernia. Atypical physical findings and computed tomography data help in the diagnosis of an interparietal inguinal hernia. The laparoscopic approach is useful and feasible for both the diagnosis and treatment of interparietal inguinal hernia.